2005
DOI: 10.1080/01411590500288809
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of nanostructured magnetic hollow microspheres: experiment and simulation

Abstract: This paper presents the experimental realization of magnetic hollow microspheres. Starting from core-shell microspheres with an organic core and a shell composed of nanoparticles, we could remove the core using a plasma etching technique. An estimate of the magnetoelastic effects arising from the interplay of magnetic dipolar interactions and cohesive energy which can be expected in such structures is given with the help of computer simulations using the Hybrid Monte Carlo method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Possible applications for this type of material are lightweight magnets or containers for magnetically guided transport of drugs or chemicals [4][5][6]. Computer simulations show that considerable deformation may be expected in the presence of magnetic fields [3] making them interesting candidates for magnetomechanical actuators or sensors, as their properties are adaptable by changing size, composition or coating of the nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Possible applications for this type of material are lightweight magnets or containers for magnetically guided transport of drugs or chemicals [4][5][6]. Computer simulations show that considerable deformation may be expected in the presence of magnetic fields [3] making them interesting candidates for magnetomechanical actuators or sensors, as their properties are adaptable by changing size, composition or coating of the nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it was shown that is possible to efficiently produce magnetic hollow microspheres consisting of a shell of magnetic nanoparticles (e.g., Fe 3 O 4 ), which are arranged on the surface of a polystyrene core in a self-assembly process [1,2]. The core was removed later using plasma etching [3]. Possible applications for this type of material are lightweight magnets or containers for magnetically guided transport of drugs or chemicals [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The amplitudes of the TE field must satisfy boundary conditions at z = 0 and z = d. Then, noting first that the Descartes-Snell relation n 1 sin i = n 0 sin † transforms (14) into † (x) = exp(i n 1 x sin i ) (17) we have at z = 0…”
Section: Te Fieldmentioning
confidence: 99%
“…that is their resistance to becoming demagnetized. The non existence of magnetic monopoles prevents to imagine the doping of these films as made of nano dots and, we have instead to consider magnetic hollow nano spheres [12][13][14][15][16][17]. Then, the permeability (z) in 0 z d may be represented by the expansion…”
Section: Magnetic Nano Composite Filmsmentioning
confidence: 99%
See 1 more Smart Citation